2022
DOI: 10.1371/journal.pone.0273209
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the knowledge, attitude and practice towards disaster medicine preparedness and readiness: A prescriptive insight by the community pharmacists in the United Arab Emirates

Abstract: Background Proper disaster preparedness by community pharmacists has the potential to counter many of the factors that cause threats and high-risk outcomes. Their preparedness and awareness may also help health practitioners and governments to improve disaster response planning. Objectives This aims to explore the knowledge, attitude, and practice (KAP) towards disaster medicine preparedness and readiness among community pharmacists in the United Arab Emirates (UAE). Method A cross-sectional study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Their responsibilities extend beyond dispensing medications under established protocols. Pharmacists also offer counseling and guidance to patients regarding medication usage, addressing any concerns or queries related to treatment and medications [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Their responsibilities extend beyond dispensing medications under established protocols. Pharmacists also offer counseling and guidance to patients regarding medication usage, addressing any concerns or queries related to treatment and medications [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted in the UAE in 2010 revealed that there were 2000 active community pharmacies ( Jairoun et al, 2022 ). To ensure adequate representation of the pharmacies in this research, the stratified random sampling technique was employed.…”
Section: Methodsmentioning
confidence: 99%